Deterrence under nuclear asymmetry: THAAD and the prospects for missile defense on the Korean peninsula. Issue 2 (3rd April 2019) - Kim, Inwook; Park, Soul
ABSTRACT: The 2016 decision to deploy Terminal High Altitude Area Defense (THAAD) to South Korea has generated multitude of intensely politicized issues and has proved highly controversial. This has made it challenging to alleviate, let alone clarify, points of analytical and policy tensions. We instead disaggregate and revisit two fundamental questions. One is whether THAAD could really defend South Korea from North Korean missiles. We challenge the conventional "qualified optimism" by giving analytical primacy to three countermeasures available to defeat THAAD–use of decoys, tumbling and spiral motion, and outnumbering. These countermeasures are relatively inexpensive to create but exceedingly difficult to offset. Second, we assess the optimal way to ensure South Korean national security against North Korean missiles. By examining the balance of capability and issues of credibility/commitment, we show that the U.S. extended deterrence by punishment remains plentiful and sufficiently credible even without enhancing the current defense capability.